Mass Media and Intensive Mothering Predict Motivators of Mother Engagement in Children's Education. - Filik-Uyanık, Rabia; Demircan, Hasibe Ö. (Journal of Child & Family Studies, 2021)
The aim of this exploratory and descriptive study was to investigate the links between motherhood-related variables and the determinants of the motivators behind mothers' engagement decisions related to their children's education. Specifically, the purpose of the study was to examine the associations between mothers' media exposures and belief systems and the motivators of their engagement decisions. In a quantitative study of 1027 mothers (M 32.91 years) with young children, the participants reported their media exposures and maternal belief systems, along with the factors motivating their engagement decisions within the first level of Hoover–Dempsey and Sandler's parent involvement model. Path analysis (LISREL) revealed that mass media and maternal belief systems predicted the motivators influencing mothers' engagement in their children's education. However, the majority of the variables were not associated with their perceptions of invitations from school experts, i.e., teachers and schools. The results of the current study indicated a paradox in the family engagement process. On the one hand, mothers' media exposures and intensive motherhood ideologies were associated with their commitment to be a part of their children's education. On the other hand, their media exposures and intensive motherhood ideologies highlight their concerns regarding invitations of school professionals in a less caring way. Highlights: Children's education involves a wide range of social systems, including their parents' own beliefs and the mass media. Exposure to childrearing information from the media, not from celebrity mother exposure, seems to be associated with family engagement. Intensive ideologies are correlated with mothers' commitment to participate in their children's education. Mothers' competitiveness and social comparison orientations are related to low self-efficacy for engagement capabilities.